Omissão do poder público e responsabilidade civil ambiental: um estudo sobre as ocupações urbanas irregulares em Manaus e seus impactos ambientais - Monteiro, Hediane Naiade Silva (2007)
The right to the ecological balanced environment includes the urban and natural environments. However, the relationship between the housing right, inherent to the constitution of the cities, and the protection of the natural environment is in disharmony. For the lack of public politics, among others aspects, Manaus grew without the due urban planning. Contributing in this disordered growth, there are irregular urban occupations. The present study has the target to demonstrate the environment civil responsibility of the Public Power of Manaus for its omission in promoting the adequate urban order of its territory, causing damages to urban and natural environments in this city. For this, it is intended to point out the competence to promote the urban order, in its aspects constitutional and legal. Also the exercise of this ability for the functions or powers of the State in this scope will be analyzed. Situated this duty, we will study its failure through the analysis of the urban disordered development of Manaus as city and the environment damages caused by the invasions in its territory. In view of that the environment damage represents one of the requirements of the objective responsibility, remains the evidence on the presence of the other requirements: omission and causality nexus. Also these requirements exists, when we conclude, for example, that the urban sustainable is threatened by the “invasion industry”. In a similar way, for the consolidation of these occupations, great areas are deforested, committing seriously the natural resources, as the urban forests. This analysis is eminently bibliographical and will be based on research in public agencies, whose performance in disordered occupations in Manaus. As well as the particular ones, in the Rule of Law, the Public Power must be submitted to the legal forecasts and assume the consequences of its omission. The care with the urban space, so important as the guardianship of the natural environment, must leave of being seen as only urban politics, passing to be faced as what in fact it is: one constitutional duty. Key words: Envoronment competence – irregular urban ocupations – environmental responsability